A short review on encapsulation of bioactive compounds using different drying techniques - S. K., Abdul Mudalip; M. N., Kathiman; N. A., Hashim; R., Che Man; Z. I. M., Arshad (Elsevier Ltd, 2021)
Bioactive compounds such as antioxidants and antimicrobial are found in food and herbal plant sources demonstrate great importance to human health. Drying techniques such as spray drying and freeze drying have been used to encapsulate the bioactive compounds from these sources for commercialization purposes. Encapsulation protects bioactive compounds from degradation and contribute to control release technology as well as development of better quality products. In this work, we reviewed the procedure as well as advantages and disadvantages of spray drying and freeze drying techniques to encapsulate the bioactive compounds extracted from the food and herbal plant sources. This review also provides insight into the latest research on encapsulation using both techniques, which is expected to offer significant information to those working in food and herbal products processing domain.